2015
DOI: 10.5539/elt.v8n8p46
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Reading among ESL Learners: A Reading Strategy Heuristic

Abstract: This paper aims to gain an insight to the relationship of two different concepts about reading comprehension, namely, the linear model of comprehension and the interactive compensatory theory. Drawing on both the above concepts, a heuristic was constructed about three different reading strategies determined by the specific ways the literal, reorganisation and inferential skills of comprehension interact. The concepts of apt and smart reading strategies were introduced, which refer to two possible ways of compe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…These activities greatly affect the student's initial knowledge and their reading comprehension ability after they received treatment. This is in line with some previous research results (Amiryousefi, 2014;Ismail, 2015;Tracey, 2017). They found that during the learning process and after learning, most students in the experimental group had better reading comprehension, were enthusiastic, active, and enjoyed reading text using the ICM.…”
Section: The Effect Of Icm-based Integrated Thematic Learning Devices On Students' Reading Comprehension On Information Textsupporting
confidence: 94%
See 1 more Smart Citation
“…These activities greatly affect the student's initial knowledge and their reading comprehension ability after they received treatment. This is in line with some previous research results (Amiryousefi, 2014;Ismail, 2015;Tracey, 2017). They found that during the learning process and after learning, most students in the experimental group had better reading comprehension, were enthusiastic, active, and enjoyed reading text using the ICM.…”
Section: The Effect Of Icm-based Integrated Thematic Learning Devices On Students' Reading Comprehension On Information Textsupporting
confidence: 94%
“…This model is a basic form to develop integrated thematic learning devices, particularly to enhance comprehension reading skills. Some research related to this Interactive-Compensatory model has been conducted by (Stanovich, 1980;Stanovich, 1984;Simpson et al, 1983;Rieben & Perfetti, 2013;McNeil, 2012;Amiryousefi, 2014;Ismail et al, 2015;Tracey & Morrow, 2017). In general, they stated that to improve students' reading comprehension to read informational text, ICM can be applied.…”
Section: Introductionmentioning
confidence: 99%
“…To master reading comprehension, a learner needs to have some intellectual abilities. These intellectual abilities are what experts identify as factors affecting reading comprehension (Aziz, Daud, & Ismar, 2019), and as a result of a wide variety of cognitive processes in our minds (Ismail, Petras, Mohamed, & Eng, 2015).…”
Section: Reading Skillmentioning
confidence: 99%
“…According to these taxonomies, while literal comprehension focus on decoding explicit information from the text through recognition or recall of its details, interpretive/inferential skills include the use of these details for the analysis, synthesis and classification of the text-based information, enabling the reader to access additional information by mapping the text. At the higher levels of cognitive processes (critical comprehension), anticipations and hypotheses are inferred by the reader beyond the explicit meaning, opinions are formed about the quality and accuracy of the text (Ismail, Yusof, Abdul Rashid & Lin, 2015).…”
Section: Theoretical Backgroundmentioning
confidence: 99%